2008
DOI: 10.1177/070674370805301007
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Body Mass Index, Mental Health, and Functional Disability: A European Population Perspective

Abstract: This is the first cross-national study investigating the role between BMI, mental disorders, and functional disability in the general population. Being overweight or obese is a common condition in the 6 ESEMeD countries. Although there is a moderate association between obesity and mental disorders, BMI did not independently influence functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 51 publications
2
32
0
6
Order By: Relevance
“…We found three additional studies through bibliography hand-searches, yielding 16 relevant publications for this systematic review. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Inter-rater agreement was good for study screening (kappa statistic 0.72, 95% CI: 0.57-0.87) and for quality assessment (kappa 0.75, 95% CI: 0.62-0.88). Tables 1 and 2 summarize the characteristics and main findings of the prospective and cross-sectional studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found three additional studies through bibliography hand-searches, yielding 16 relevant publications for this systematic review. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Inter-rater agreement was good for study screening (kappa statistic 0.72, 95% CI: 0.57-0.87) and for quality assessment (kappa 0.75, 95% CI: 0.62-0.88). Tables 1 and 2 summarize the characteristics and main findings of the prospective and cross-sectional studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies showed a significant positive association [30][31][32]39,[41][42][43] while five showed a positive trend that was nonsignificant for at least one gender stratum. 34,35,37,44,45 In the largest study on obesity and anxiety disorder to date, Zhao et al 45 analyzed data from 177 047 American adults. Participants self-reported any lifetime medically diagnosed anxiety disorder.…”
Section: Study Selectionmentioning
confidence: 99%
“…In addition, the study of De Girolamo et al (14) did not address the distribution of psychiatric diagnoses according to different BMI categories. The relationship between BMI and mental health has been investigated in the European Study on the Epidemiology of Mental Disorders (ESEMeD) (15) , which included the ISTAT findings in the Italian population. In keeping with other reports (8)(9)(10) , the ESEMeD study found that obese subjects were 30-40 % more likely to suffer from one or more mental disorders compared with normalweight subjects (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between BMI and mental health has been investigated in the European Study on the Epidemiology of Mental Disorders (ESEMeD) (15) , which included the ISTAT findings in the Italian population. In keeping with other reports (8)(9)(10) , the ESEMeD study found that obese subjects were 30-40 % more likely to suffer from one or more mental disorders compared with normalweight subjects (15) . Although we have excellent epidemiological data on the prevalence of mental disorders in obese subjects (16)(17)(18) and in the general population (14) , less is known about outpatient populations and the distribution of psychiatric diagnosis according to DSM-IV-TR criteria (12) in normal-weight and underweight subjects who wish to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity (BMI ≥ 30) is associated with mood disorders in community studies Bruffaerts et al, 2008;De Wit et al, 2010;Johnston et al, 2004;Luppino et al, 2010;Petry et al, 2008;Simon et al, 2006), although the relationship is affected by several confounding factors, especially gender. In women, depression is significantly associated with BMI, but in men it often is not Jorm et al, 2003;Lim et al, 2008;McLaren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%